This land is your land - Guthrie, Woody, 1912-1967; Jakobsen, Kathy (Boston, Mass. : Little, Brown and Co., 1998)
This well-known folk song is accompanied by a tribute from folksinger Pete Seeger, the musical notation, and a biographical scrapbook with photographs.
Includes musical notation.
NP
Accelerated Reader AR
Keywords: Guthrie, Woody, -- 1912-1967.; Folk songs -- United States